Students’ commognition in solving linear programming question - Achmad Ghozi Khoiruddin; Ali Shodikin; Evangelista Lus Windyana Palupi (Jurnal Elemen, 2026)
Although mathematical communication is considered important, students still struggle to express mathematical ideas effectively. Therefore, this research is going to use a commognitive framework that provides a valuable lens for analyzing and enhancing students' mathematical communication skills. The purpose of this study is to describe students' cognition in solving linear programming problems. The researcher selected six students for interviews based on the consistency of their answers and then selected two students from the six students who had been interviewed. Commognitive analysis shows striking differences in mathematical thinking and communication between DAJ and ED subjects, who are students with high and low commognitive abilities, respectively. Students with high commognitive abilities tend to be more comprehensive and exploratory. In contrast, a student with low commognitive ability is relatively more limited and procedural. This implies that teachers cannot judge understanding only by whether students reach the correct answer. They must also attend to how students talk, write, and represent mathematics, since these discursive moves reveal whether their routines are genuinely conceptual or merely imitative. As a result, it is advised that future studies include a group discussion, better-developed question types, and more specified student criteria.